2014
DOI: 10.17305/bjbms.2014.3.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topically applied sildenafil citrate on wound healing: experimental study

Abstract: Wound healing is a complex process that necessitates organization of different cell types and several signalling molecules. The aim of this study is to evaluate the effect of different concentrations of sildenafil citrate, which decreases cGMP degradation, on wound healing by secondary intention.This study was performed using 25 Sprague Dawley rats weighing 200-250 grams. 4 dorsal defects were created. Four different treatment modalities which were 1% and 5% sildenafil citrate gel prepared with carbopol, pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
15
0
2
Order By: Relevance
“…Moreover, it was observed for in vitro wound healing assays that NO donors can speed up cell migration and collagen deposition [101, 102]. Application of sildenafil cream (inhibitor of cGMP specific phosphodiesterase type 5 - PDE5) on human epidermal injuries has been found to result in faster wound healing [103]. We were not able to reproduce a significant faster healing in embryos through the use of the NO donor, S-Nitroso-N-acetylpenicillamine (SNAP).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was observed for in vitro wound healing assays that NO donors can speed up cell migration and collagen deposition [101, 102]. Application of sildenafil cream (inhibitor of cGMP specific phosphodiesterase type 5 - PDE5) on human epidermal injuries has been found to result in faster wound healing [103]. We were not able to reproduce a significant faster healing in embryos through the use of the NO donor, S-Nitroso-N-acetylpenicillamine (SNAP).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (20) showed that necrosis developing in ischemia-reperfusion damage of NO can be prevented by c-GMP and the guanylate cyclasedependent kinase pathway. Gursoy et al (21) researched the impact of sildenafil on wound recovery and showed that sildenafil makes a positive contribution by increasing the neovascularization and abdominal wall tensile force. Cakir et al (22) stated that sildenafil had a histopathologically positive impact on colon anastomosis recovery.…”
Section: Discussionmentioning
confidence: 99%
“…O fármaco citrato de sildenafila (CS) pode representar uma terapia de resgate em pacientes que não respondem a terapia epitelial convencional. Alternativamente, ele também pode ser a primeira escolha em pacientes nos quais outros medicamentos são contraindicados ou de difícil acesso, concordando com Gürsoy et al (2014) e Farsaei et al (2015 que referem ser o CS um novo agente para tratamento de feridas abertas devido sua facilidade de administração e efeitos colaterais aceitáveis.…”
Section: Diaunclassified
“…Esse processo inclui o óxido nítrico (NO) que contribui para a vasodilatação e neoangiogênese, além de auxiliar na regulação, proliferação celular, síntese de colágeno e epitelização (FARSAEI et al, 2015). Como o CS aumenta a liberação de NO, está sendo usado para o reparo de lesões (GÜRSOY et al, 2014).…”
Section: Introductionunclassified